2012
DOI: 10.1590/s0034-737x2012000500004
|View full text |Cite
|
Sign up to set email alerts
|

Análises técnicas e econômicas no sistema de integração lavoura-pecuária submetido à adubação nitrogenada

Abstract: Technical and economic analysis in integrated crop-livestock submitted to nitrogen fertilizationSustainable agriculture, reduced production costs and adding value to the system are achieved through the use of agricultural areas throughout the year, in integrated or mixed system. The study aimed to determine the technical coefficients to estimate and evaluate the operational cost and profitability indicators of the consortium of corn with two species of Brachiaria (B. brizantha, MG-5 and B. ruziziensis). The cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…However, in corn production systems, the need for fertilizers is known as one of the factors that increases the production costs (COSTA et al, 2012b); in addition, its misuse can cause environmental harm. However, it is known that inoculating corn seeds with diazotrophic bacteria can improve the crop nitrogen supply (DARTORA et al, 2013;KAPPES et al, 2013) and can thereby reduce the need for externally applied nitrogen fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…However, in corn production systems, the need for fertilizers is known as one of the factors that increases the production costs (COSTA et al, 2012b); in addition, its misuse can cause environmental harm. However, it is known that inoculating corn seeds with diazotrophic bacteria can improve the crop nitrogen supply (DARTORA et al, 2013;KAPPES et al, 2013) and can thereby reduce the need for externally applied nitrogen fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, for the efficient implementation and management of NTS, crop rotation using species with high potential for straw production and high C/N ratio is essential to ensure soil coverage for a longer period. Corn (Zea mays) and the brachiarias Urochloa brizantha and Urochloa ruziziensis, especially the latter, stand out for the easy drying and less tiller cluster formation, which promote a more uniform soil coverage and facilitate the next crop sowing (Fiorentin et al, 2011;Costa et al, 2012b;Rodrigues et al, 2012;Sabundjian et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This grass species does not regenerate as fast as 'Mombaça' grass, and it produces straw that inhibits weed development. Costa et al (2012) also observed that the yield of beans increased when they grew on straw from forages of the genus Urochloa.…”
Section: Resultsmentioning
confidence: 84%
“…Fifty-three percent of the operational costs were invested in the harvest, and 74% of the input costs were invested in pest control products, soil-acidity amelioration, and fertilizers. Since corn is highly dependent on soil fertility for maximum yield (Costa et al, 2012), and it does not fix nitrogen, it demanded the highest fertilizer costs of the three crops studied. The profitability indicator data are presented in Table 4.…”
Section: Resultsmentioning
confidence: 99%